IMPACT OF THE COVID-19 PANDEMIC ON VITAMIN D LEVELS IN CHILDREN OF RYAZAN - N.A. BELYKH; I.V. PIZNYUR; V.V. MAYBORODA; O.A. SOLOVYOVA (Avicenna Tajik State Medical University, 2024)
Objective: To evaluate the effect of staying at home during the COVID-19 pandemic on serum 25(OH)D levels in children permanently residing in Ryazan. Methods: The study included 279 children aged 2 to 17, who were divided into two groups: in Group 1, serum 25(OH)D level was tested before the COVID-19 pandemic, while in Group 2, it was assessed during a pandemic. Results: The median serum 25(OH)D level in children of Group 1 was 1.4 times higher than in Group 2 (22.8 ng/ml vs. 16.6 ng/ml, p=0.004). The share of children with vitamin D (VD) deficiency during the pandemic home stay increased 1.4 times, while the percentage of children with optimal VD status decreased by three times. A statistically significant decrease in the median serum 25(OH)D during the pandemic was observed in children aged 2-3 years and 4-6 years (p<0.05). Conclusion: COVID-19 movement restrictions significantly decreased serum 25(OH)D levels in children.